Process-Oriented Tolerancing: Consideration of Manufacturing and Operation for Product Assurance Using Virtual Methods - Bode, Christoph; Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Research in Tolerancing, 2024)
A product generally proceeds through development, production and assembly before it goes into operation. In particular, iterations often occur between development and production, although information are usually only passed on systematically in one direction. Errors during development and especially during tolerancing, scheduled at the end of the development phase, are therefore usually not discovered until production, assembly, or operation. The risk of such errors is particularly high in tolerancing for two reasons. First, tolerancing is usually based on expert knowledge or standards, which covers a large proportion of standard cases, but not every case. Second, conventional tolerancing usually focuses on ensuring functionality at the end of production. The manufacturability and the influence of operation in terms of wear are usually not considered. The aim of process-oriented tolerancing is to provide information from production and operation early in the development phase and especially in tolerancing. This enables the tolerance engineer to ensure manufacturability and functionality before and during operation. This chapter provides an overview of process-oriented tolerancing. Both state-of-the-art approaches and a novel holistic approach using virtual methods are presented. The novel approach aims to include all areas involved in tolerancing and to reduce iterations and the time required for testin